Metamorphoses of logos: from non-predicative to predicative - Santos, José Gabriel Trindade (Revista Archai, 2018)
This paper deals with some philosophical uses of logos prominent in platonic dialogues, namely those associated to contrasting logical and-epistemological contexts. Contraposed to some non-predicative conceptions, the ‘predicative’ theory of logos (Sophist 261-264) culminates Plato’s research on the subject. In the “socratic” dialogues it focuses on the request to answer the “What is?” question with a logos, to which corresponds, in the Phaedo and the Republic, the logon didonai requirement as proof of knowledge. As examples of sophistic uses of logos it examines three infallibilist and non-referentialist conceptions of logos advanced in the Euthydemus, the Theaetetus and the Cratylus. Having analyzed three cases of non-predicative logos, the paper suggests that with the predicative theory of logos Plato aims at enabling discourse to get at the knowledge of “what is”.